Development Macroalgae Diversity Leaflet on East Coast Pacitan to Improve Students’ Conceptual Understanding of Local Biodiversity - Ezif Rizqi Imtihana; Restiana Restiana; Rizka Amiliya Febriani (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2026)
This study aims to develop biodiversity topic leaflet by integrating local potential, macroalgae to increase insight into local biodiversity. This study is R&D using modified ADDIE approach. Stages of this study consist of analysis, design, and development. Data collection uses teacher and student needs analysis questionnaires, expert validation questionnaires, teacher assessments and student responses. The data analysis techniques used qualitative and quantitative. Qualitative analysis is based on data analysis while quantitative is based on validation and practicality of leaflet. The trial of use was conducted in class IV MI Muhammadiyah Gawang, Pacitan, East Java. Results of the study showed that (1) characteristics of leaflet developed were interactive such as visualization of real images like the original. (2) results of leaflet validation test on validator 1 were 93.35% with very good criteria, and validator 2 was 97.23% with very good criteria. (3) the average percentage obtained from results of practicality test by teacher was 76.19 with practical criteria. (4) the percentage of scores obtained from student responses was 91.66% with very good criteria. Based on the research results, this leaflet is suitable as learning media that teaches concept of biodiversity based on local potential